The preparation and structural studies in the (80 - x)TeO2-20ZnO-(x)Er2O3 glass system - Sahar, Md Rahim; Sulhadi, K.; Rohani, M.S. (Elsevier B.V., 2008)
Er3+-doped tellurite glasses of the (80 − x)TeO2–20ZnO–(x)Er2O3 system (0.5 mol% less-than-or-equals, slant x less-than-or-equals, slant 2.5 mol%) have successfully been made by melt-quenching technique and their structure has been investigated by means of DTA and Raman spectroscopy. The DTA results show the thermal parameters; such as the glass transition temperature (Tg) and crystallization temperature (Tc) were determined. It is found that this system provides a stable and wide glass formation range in which the glass stability around 99–140 °C may be obtained. The Raman spectroscopy used the structural studies in the glass system. Two Raman shift peaks were observed around 640–670 cm−1 and 720–740 cm−1, which correspond to the stretching vibration mode of TeO4 tbp and TeO3 tp, respectively. It is found that the spectral shift in Raman spectra is depending on the Er2O3 content. This evolution is an indication of the changes in the basic unit of the glass structure.